Evaluating the rheological, chemical and mechanical properties of hybrid asphalt binders and mixtures for enhanced performance - Wan Noor Hin, Mior Sani; Putra Jaya, Ramadhansyah; Khairil Azman, Masri; Amar, Dulaimi (Springer Nature Switzerland AG, 2025)
Waste materials in asphalt mixtures have garnered significant interest due to environmental concerns and the necessity for sustainable infrastructure. This study evaluated the performance of a waste material-based hybrid asphalt mixture, including palm oil fuel ash (POFA), garnet waste, and sawdust. Numerous physical tests were conducted to examine the hybrid asphalt mixture characteristics, such as penetration, softening point, and viscosity assessments. Rheological properties of the hybrid asphalt binders were analysed using a Dynamic Shear Rheometer (DSR), while microstructural characteristics were examined through scanning electron microscopy (SEM) and atomic force microscopy (AFM). A Marshall stability tests were then performed to evaluate the mechanical stability of the hybrid asphalt mixture under load-bearing conditions. Consequently, the hybrid asphalt mixture demonstrated favourable outcomes in improving the hot mix asphalt characteristics. These findings suggested that the hybrid contents (0% as control, 3%, 6%, and 9%) produced a significant performance impact on the hybrid asphalt mixture. DSR testing revealed that the 6% hybrid asphalt binder exhibited enhanced rutting resistance and elasticity, with higher complex modulus (G*) and lower phase angle (δ), indicating improved performance under high-temperature conditions. The 6% hybrid asphalt mixture demonstrated the highest stability, achieving a Marshall stability of 22.33 kN and showing enhanced resistance to aging, attributed to the binder’s sensitivity to test temperatures. Additionally, SEM and AFM analyses revealed robust particle adhesion and interactions within the 6% hybrid asphalt mixture, indicating improved structural cohesion. This study effectively demonstrated that the waste materials (POFA, garnet waste, and sawdust) in the hybrid asphalt mixtures developed enhanced physical and mechanical characteristics.